Racial Discrimination of White against Black in Jericho Brown and Emtithal Mahmoud’s Selected Poems - Yunis Stia Andara; Yan Ardian Subhan (Universitas Cokroaminoto Palopo, 2023)
The purpose of this study is to depict the issues of racial discrimination from white to black and their struggle and resistance against it in selected poems. The poems are taken from The Tradition (2019) by Jericho Brown and Eulogy (2018) by Emtithal Mahmoud. This study collected and analyzed data using qualitative research that explains the data into essay descriptions. This study uses a Postcolonial perspective from Loomba's theory of racial discriminations seen from contexts of identity, race, and class (2015). The results of this study indicate that in selected poems from Jericho Brown and Emtithal Mahmoud describe issues of multiple acts of racial discrimination since colonial era, being positioned in the lower economic class, and experiencing genocidal practices. In the end, the discriminated black people struggle and resist against their oppressors for equality.